Islamic Ethical Governance of Post-Disaster Recovery: Advancing Inclusive Education, Gender Equality, and Decent Work for Vulnerable Communities - Ellectrananda Anugerah Ash-shidiqqi; Ahmad Nailul; Joko Ismono; Suryanti Suryanti; Indra Budi Jaya (Mawaddah: Jurnal Hukum Keluarga Islam, 2026)
Natural disasters generate profound socio-economic disruptions that disproportionately affect vulnerable workers, including informal laborers, women, persons with disabilities, and low-income communities. Despite growing attention to disaster governance and social protection, existing frameworks remain fragmented and often lack an ethical foundation capable of integrating social justice, economic inclusion, and long-term resilience. This study aims to develop an integrative conceptual model grounded in Islamic ethics to support inclusive post-disaster recovery for vulnerable workers. Employing a normative-conceptual approach, the study analyzes relevant scholarly literature, the Sustainable Development Goals (SDGs 4, 5, and 8), and Islamic legal-ethical perspectives. The findings propose a framework that synthesizes three core Islamic ethical principles ‘adl (justice), ta‘āwun (mutual cooperation), and maṣlaḥah (public welfare) with four interrelated pillars: inclusive education, gender equality, decent work, and disaster resilience. The model demonstrates that inclusive education enhances adaptive capacity, gender equality promotes equitable participation and access, decent work facilitates sustainable livelihood recovery, and disaster resilience strengthens long-term socio-economic stability. Theoretically, this study advances the discourse on Islamic social protection by bridging Islamic ethical principles with contemporary development and disaster recovery agendas. Practically, it offers a culturally grounded and value-based framework for policymakers and humanitarian actors seeking to design more equitable, inclusive, and sustainable recovery strategies. The proposed model contributes to the development of ethically informed disaster governance that prioritizes human dignity, social protection, and economic inclusion for vulnerable populations.